2006
DOI: 10.1380/ejssnt.2006.636
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characteristics study of ZnO: (Al, Cu, I) thin films by chemical spray pyrolysis

Abstract: Spray pyrolysis deposition technique has been used to grow ZnO thin films doped with different dopant species (Al, Cu, I). The optical and electrical properties of films were investigated as function of dopant type and concentration. The structural characteristics of undoped and doped ZnO films were studied using X-ray diffraction (XRD). The electrical resistivity as low as 4 × 10 −2 Ωcm was obtained for ZnO:Al with 5 at.% dopant concentration. ZnO:Cu films prepared at specific conditions exhibited p-type cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
(19 reference statements)
1
1
0
Order By: Relevance
“…The photodetector responsivity as a function of wavelength before and after RTA is depicted in figure 7. The shape of spectral responsivity was very close to the transmittance spectrum of the Al:ZnO film deposited on the glass especially in the UV-VIS region [19]. It shows that a detection process takes place in the UV and visible regions.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The photodetector responsivity as a function of wavelength before and after RTA is depicted in figure 7. The shape of spectral responsivity was very close to the transmittance spectrum of the Al:ZnO film deposited on the glass especially in the UV-VIS region [19]. It shows that a detection process takes place in the UV and visible regions.…”
Section: Resultssupporting
confidence: 59%
“…Optical and electrical properties of ZnO:Al films were reported recently [19]. The Hall measurement revealed that the conductivity of the ZnO:Al films is n-type.…”
Section: Resultsmentioning
confidence: 93%